Plants that can be Poisonous for Cows. A Review - Cristina EL MAHDY; Silvana POPESCU; Cristin BORDA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2017)
Romania is blessed with a rich spontaneous flora, but some of the plants are toxic by their consumption in cattle, affecting the health, productions and endangering consumer safety. Sometimes even the consumption of small amounts causes poisoning with a broad extension: from mild, moderate to severe and with chronic or acute manifestations. Plant action is not similar. Taxus Buccata, Eupatorium spp. (E. rugosum, E. urticaefolium, E. ogeratoides) are cardiotoxic plants, but, Eupatorium spp. also acts through depression of the central nervous system; Datura stramonium (Jimson weed), Solanum spp. (nightshades), Atropa belladonna (belladonna), are plants with cholinergic blocking; haemolytic anemia is caused by Pteridium aquilinum (Bracken fern) and Equisetum (horsetail). The poisoning with cyanogenic principles occurs at Sorghum spp (Johnson grass, sudan grass); Elderberry consumption, Senecio spp. and Hypericum (St John’s wort) induces liver toxicity. Plants containing alkaloids outside their toxicity also have teratogenic action: Lupinus spp., Nicotiana spp, Conium maculatum, Veratrum album. However, some of these plants can be used in certain cows’ treatments.